Prawne możliwości zaskarżenia przez radnego uchwał podejmowanych przez organ stanowiący jednostki samorządu terytorialnego, w którego skład wchodzi - Kłosowiak, Miłosz; Krauschar, Kamil (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
In the public sector, in the hierarchy of local government units, the commune plays a key role in the administrative division of the state and constitutes its basic unit. Apart from communes, the legislator distinguishes poviats and voivodships to which their own tasks have been assigned and commissioned, not reserved by separate acts for other entities. The organizational level of local government covers the relevant territory of a given unit, and above all applies to residents who by law belong to the local (regional) community. Representation of the community takes place through the bodies of local government units elected in general elections. These include the decision-making body and the executive body. The body constituting a local government unit consists of councilors who are obliged to be guided by the good of the local government community. The article contains selected issues of the legal determinants of exercising the mandate of a councilor and its impact on the decision-making process of the council. The aim of the paper is to obtain answers to the questions: (1) what are the legal possibilities for a councilor to challenge resolutions adopted by the decision-making body of the local government unit they are a part of?; (2) does the councilor have a complaint card based on violation of a legal interest or entitlement? Assessing the properties and prerogatives of a councilor resulting from the exercise of the mandate will highlight the issues related to the activity (complaints) of a councilor or a group of councilors regarding actions taken as part of the legislative processes of a given local government. As a supplement to the considerations made based on the position of the doctrine, an analysis of the current judicial directions of administrative courts was conducted. A comprehensive approach to the discussed issue is an attempt to indicate the correct interpretation of the law in regards to exercising the mandate of a councilor and their influence (complaints) on the resolution-making process of the council.
Keywords: local government units; complaint; councilor; council; resolution